evoke and evoke+: design of two large-scale, double-blind, placebo-controlled, phase 3 studies evaluating efficacy, safety, and tolerability of semaglutide in early-stage symptomatic Alzheimer’s disease - Jeffrey L. Cummings; Alireza Atri; Howard H. Feldman; Oskar Hansson; Mary Sano; Filip K. Knop; Peter Johannsen; Teresa León; Philip Scheltens (Alzheimer’s Research & Therapy)
Abstract Background Disease-modifying therapies targeting the diverse pathophysiology of Alzheimer’s disease (AD), including neuroinflammation, represent potentially important and novel approaches. The glucagon-like peptide-1 receptor agonist semaglutide is approved for the treatment of type 2 diabetes and obesity and has an established safety profile. Semaglutide may have a disease-modifying, neuroprotective effect in AD through multimodal mechanisms including neuroinflammatory, vascular, and other AD-related processes. Large randomized controlled trials are needed to assess the efficacy and safety of semaglutide in early-stage symptomatic AD. Methods evoke and evoke+ are randomized, double-blind, placebo-controlled phase 3 trials investigating the efficacy, safety, and tolerability of once-daily oral semaglutide versus placebo in early-stage symptomatic AD. Eligible participants were men or women aged 55–85 years with mild cognitive impairment or mild dementia due to AD with confirmed amyloid abnormalities (assessed by positron emission tomography or cerebrospinal fluid [CSF] analysis). After a maximum 12-week screening phase, an anticipated 1840 patients in each trial are randomized (1:1) to semaglutide or placebo for 156 weeks (104-week main treatment phase and 52-week extension). Randomized participants follow an 8-week dose escalation regimen (3 mg [weeks 0–4], 7 mg [weeks 4–8], and 14 mg [weeks 8–156]). The primary endpoint is the semaglutide–placebo difference on change from baseline to week 104 in the Clinical Dementia Rating – Sum of Boxes score. Analyses of plasma biomarkers, collected from all participants, and a CSF sub-study (planned n = 210) will explore semaglutide effects on AD biomarkers and neuroinflammation. Results Enrollment was undertaken between May 18, 2021, and September 8, 2023. Completion of the trials’ main phase is expected in September 2025, and the 52-week extension (in which participants and investigators remain blinded to treatment assignment) will continue to October 2026. Conclusion evoke and evoke+ are the first large-scale trials to investigate the disease-modifying potential of semaglutide in participants with early-stage symptomatic AD, including exploration of effects on AD biomarkers and neuroinflammation. The trials will provide data on the potential disease-modifying effects of semaglutide and will be important in evaluating its utility in the treatment of early-stage symptomatic AD. Trial registration Clinicaltrials.gov, NCT04777396 and NCT04777409. Date: 02/03/2021